Dampak Kebijakan Diskon Tarif Listrik Terhadap Konsumsi Listrik di Kota Semarang - Nabila Dwi Astuti; Deky Aji Suseno (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the impact of the 50% electricity tariff discount policy on household electricity consumption in Semarang City using income, number of dependents, and ownership of electronic devices as variables. This study uses a quasi-qualitative analysis method with the help of Nvivo 12 software. The data used are primary data with data collection methods, namely questionnaires and interviews with 101 informants of prepaid customers of class R-1 (450 VA, 900 VA, 1,300 VA, and 2,200 VA) in Semarang City. The results of this study indicate that the electricity tariff discount policy affects changes in the amount and pattern of electricity consumption in Semarang City. In addition, the income variable affects the ability and decision to consume electricity. The number of dependents affects electricity consumption based on the tendency of members who are active at home. Ownership of electronic devices also affects changes in electricity use, ranging from more flexible use to continuing to save. Overall, the 50% electricity tariff discount policy has been proven to have a significant impact on household electricity consumption in Semarang City which is influenced by the economic and demographic characteristics of the household..